2020
DOI: 10.1186/s13098-020-00561-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intracellular toxic advanced glycation end-products (TAGE) on murine myoblast cell death

Abstract: Background: Sarcopenia is a progressive condition that is characterized by decreases in skeletal muscle mass and function. Although sarcopenia is associated with lifestyle-related diseases (LSRD), the mechanisms underlying cell death in myoblasts, which differentiate to myotubes, remain unclear. We previously designated glyceraldehyde (an intermediate of glucose/fructose metabolism)-derived advanced glycation end-products (AGEs) as toxic AGEs (TAGE) because of their cytotoxicity and involvement in LSRD, and hy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 37 publications
1
63
1
Order By: Relevance
“…Therefore, effects of intracellular TAGE in the kidney was not analyzed. However, the amount of intracellular TAGE which can induce cell death was more than 6.0 μg/mg protein in the hepatic cells, pancreatic cells, cardiomyocytes, and myoblasts cells [ 17 , 18 , 20 , 21 ]. Since if intracellular TAGE were generated in the kidney, they might not induce cell death of dramatically dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, effects of intracellular TAGE in the kidney was not analyzed. However, the amount of intracellular TAGE which can induce cell death was more than 6.0 μg/mg protein in the hepatic cells, pancreatic cells, cardiomyocytes, and myoblasts cells [ 17 , 18 , 20 , 21 ]. Since if intracellular TAGE were generated in the kidney, they might not induce cell death of dramatically dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we focused the blood TAGE which may be secreted/released from organs which generated intracellular TAGE [ 15 , 21 ]. One study reported that TAGE in the blood promoted the apoptosis of human renal mesangial cells in vitro [ 11 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We postulate that non-toxic AGE structures may be physiologically relevant for preventing the potentially damaging consequences of the advanced glycation process. CEL: Nε-(carboxyethyl)lysine; MG-H1: methylglyoxal-hydroimidazolone; MOLD: methylglyoxyl-derived lysine dimer; GOLD: glyoxyl-derived lysine dimer Takeuchi Diabetol Metab Syndr (2020) 12:105 neuronal cell damage [32], but also hepatocellular damage [33][34][35] and pancreatic ductal epithelial cell damage [36], cardiomyocyte pulsation arrest and cell death [37], and myoblast cell death [38]. Therefore, TAGE are accumulate in cells, cause cell damage, and leak extracellularly into the blood, thereby increasing TAGE levels in circulating fluids.…”
Section: Concepts Of Non-toxic Ages and Tagementioning
confidence: 99%
“…More recently, we demonstrated that intracellular TAGE formation and accumulation induced not only neuronal cell damage [ 32 ], but also hepatocellular damage [ 33 35 ] and pancreatic ductal epithelial cell damage [ 36 ], cardiomyocyte pulsation arrest and cell death [ 37 ], and myoblast cell death [ 38 ]. Therefore, TAGE are accumulate in cells, cause cell damage, and leak extracellularly into the blood, thereby increasing TAGE levels in circulating fluids.…”
Section: Concepts Of Non-toxic Ages and Tagementioning
confidence: 99%